Optimizing the Role of the Village-Owned Enterprise (Bumdes) Mitra Mandiri Sajau in Efforts to Improve Community Welfare (Case Study in Sajau Village, Tanjung Palas Timur District) - Suparjan, Muhammad Eri; Adji, Widwi Handari (International Journal of Science Education and Technology Management, 2025)
Sajau Village established the Mitra Mandiri Sajau Village-Owned Enterprise (BUMDes) to support village development and community welfare. This study aims to assess the effectiveness of the services offered by the Mitra Mandiri Sajau Village-Owned Enterprise (BUMDes) for the Sajau village community. This research method uses qualitative data through in-depth interviews with BUMDes management and observational data collection. The findings of this study indicate that the Mitra Mandiri Sajau Village-Owned Enterprise (BUMDes) has contributed significantly to improving community welfare, but its implementation is still imperfect. Several factors have made BUMDes management a challenge, such as the lack of management competence and the lack of management involvement in the process. Therefore, the government's role is needed to provide support and training to the Mitra Mandiri Sajau Village-Owned Enterprise (BUMDes) management regarding BUMDes management so that it runs smoothly and professionall